End Stage Renal Disease: Seroprevalence of Hepatitises B and C along with Associated Aetiology and Risk Factors in Children. (5th August 2015) - Shah, Syed Raza; Khan, Muhammad Shahzeb; Alam, Muhammad Tanveer; Salim, Adnan; Hussain, Mehwish; Altaf, Areeba
Abstract : Background . End Stage Renal Disease (ESRD) normally requires dialysis or transplantation for survival. Since ESRD patients are on long term dialysis, infections such as Hepatitis B (HBV) and Hepatitis C (HCV) are commonly reported. Methods . This was a retrospective study carried out at a government hospital during a 12-month period from January 2013 to December 2013. The data was collected using a predesigned pro forma to note the etiology, gender, age, and HBsAg and anti-HCV test result of each patient. Results . 444 children suffering from ESRD were included in our analysis. The mean age of sample was 12.7 ± 4.1 years. Sixty percent (n = 262 ) of the children were boys. The most common etiology of ESRD was kidney stones (n = 44, 29.3%). HBV was positive in 11 children (2.5%) while HCV was positive in 13 (2.9%). Conclusion . This study asserts the need for carrying out further work to confirm these findings and expand our recommendations. It is imperative to reliably determine the burden of HBV and HCV disease and to determine the aetiology of their spread especially in children with ESRD.